Metropolitan management in the Metropolitan Area of the Valley of Mexico: between legality and political will - Salinas-Arreortua, Luis Alberto (Papeles de Población; Vol. 23 Núm. 91 (2017), 2017)
Metropolitan management is one of the great challenges because of the economic, social, and above all political complexity that it represents. In the case of Mexico, it is an issue that attracts attention, however, there is no consensus on the most efficient type of metropolitan government, which, if we bear in mind, is the need for metropolitan management. However, it is important to mention that the formation of an administrative structure that manages a metropolitan area based on political-administrative boundaries and on a certain scale has been a problem for urban and metropolitan management. The objective of this text is to provide elements for the discussion of a metropolitan management for the Metropolitan Zone of the Valley of Mexico, considering mechanisms for the construction of relationships and actors at different scales, under the current legal conditions.